1995
DOI: 10.1046/j.1537-2995.1995.35795357878.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that CDw108 membrane protein bears the JMH blood group antigen

Abstract: CDw108 is expressed on red cells and resides on the same GPI-linked membrane protein as does the JMH blood group antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…37 The sema4D knockout impairs collagen-induced platelet aggregation in vitro and inhibits platelet accumulation after vascular injury in vivo. 15,38 Sema7A (CD108) was originally identified in the immune system 39 and as the JMH antigen on erythrocytes, 40 but it is also expressed by neurons and has a role in axon guidance. 41 Known binding partners for sema7A include plexin C1 42 and integrin ␣ 1 ␤ 1 .…”
Section: The Impact Of Sheddingmentioning
confidence: 99%
“…37 The sema4D knockout impairs collagen-induced platelet aggregation in vitro and inhibits platelet accumulation after vascular injury in vivo. 15,38 Sema7A (CD108) was originally identified in the immune system 39 and as the JMH antigen on erythrocytes, 40 but it is also expressed by neurons and has a role in axon guidance. 41 Known binding partners for sema7A include plexin C1 42 and integrin ␣ 1 ␤ 1 .…”
Section: The Impact Of Sheddingmentioning
confidence: 99%
“…Semaphorin-7A (CDw108) is a GPI-linked protein carrying the John-Milton-Hagen blood group antigen (Mudad et al, 1995) whose expression has also been observed on activated leucocytes as well as in the spleen, thymus, testis, placenta, brain and spinal cord (Xu et al, 1998;Yamada et al, 1999). Semaphorin-7A has an important role in the development of both the nervous and immune systems where it promotes axon outgrowth through integrins (Pasterkamp et al, 2003), and has also been implicated in the regulation of T-cell function (Czopik et al, 2006;Suzuki et al, 2007;Gras et al, 2013), bone cell differentiation (Delorme et al, 2005), spreading and dendricity in human skin melanocytes (Scott et al, 2008), nerve regeneration and inflammation processes in the cornea (Namavari et al, 2012), and GnRH-1 neuron development (Messina et al, 2011).…”
Section: Semaphorin-7a: An Erythrocyte Receptor For P Falciparum Mtrapmentioning
confidence: 99%
“…Monoclonal antibodies of the CD108 cluster of differentiation may also be considered anti -JMH [9] . A monoclonal antibody (H8), produced from a mouse immunised with a human lymphoid cell line derived from a patient with acute lymphocytic leukaemia, appeared to have the same specifi city as anti -JMH5 [23,24] .…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%